Encourage Women to Remain in Secondary Education and Create Opportunities for STEM Careers - Santos, Alessandra Ferreira dos (2023)
In this study, we intend to understand how public policies can mitigate the complex challenges linked to gender inequality in high school in Brazil. The role of public policies in dealing with gender issues is discussed, with a focus on high school, a stage that makes it possible to overcome challenges faced by women in their study trajectories, especially in STEM careers (Science, Technology, Engineering and Mathematics).